Risk Assessment in Oil and Gas Industry Using Simulation and Bow-Tie Analysis - Kbah, Zaid; Erdil, Nadiye O.; Aqlan, Faisal (International Journal of Industrial Engineering: Theory, Applications and Practice, 2020)
Risks have been in the forefront of supply chain management because of the exponential rise of natural disasters and the noticeable increase of supply chain disruptions. In oil and gas industry, risk events can be associated with consequences that might lead to fatalities and loss of millions of dollars. Therefore, effective risk management is vital for oil and gas companies. In this research, a framework that combines simulation and Bow-Tie risk modeling is proposed to study the disruption risks in oil and gas supply chains. The simulation model captures the flow of material and information and accounts for the dynamic interactions among the system components. Bow-Tie analysis is used to quantify the risks and their impact. A case study is provided to demonstrate the application of the proposed framework and to show its effectiveness as a decision-support tool that can be used in disruption risk management.